Determinants of the extent of Asia-Pacific banks' derivative activities - Hue Hwa Au Yong; Robert Faff; Keryn Chalmers (Journal of Accounting and Management Information Systems (JAMIS), 2014)
We present an analysis of the determinants of Asia-Pacific banks' extent of derivative activities. Our findings suggest that the probability of financial distress and economies of scale arguments are important in this regard. Further analyses reveal that Asia-Pacific dealer banks tend to use more foreign currency derivatives while interest rate derivatives are generally used for hedging purposes. Our findings also indicate that banks located in countries with an explicit deposit insurance scheme engage in greater derivative activities. Such behaviour may reflect either hedging or speculation.
Keywords: G21; G32; 650; Derivatives; Asia-Pacific banks; Determinants